Junie B. Jones is a beauty shop guy - Park, Barbara; Brunkus, Denise (New York : Random House, 1998)
After her first trip to a beauty parlor Junie decides she wants to work there, and she practices on her bunny slippers, her dog, and herself with disastrous results.
"A First Stepping Stone book."
390
RL: 2.0.
006-009.
Accelerated Reader AR
Keywords: Beauty shops -- Juvenile fiction; Hair -- Juvenile fiction; Kindergarten -- Juvenile fiction; Schools -- Juvenile fiction; Humorous fiction